Primula dujiangyanensis (Primulaceae) discovered from Sichuan, Southwest China - Ju, Wen-Bin; Deng, Heng-Ning; Zhu, Da-Hai; Gao, Yun-Dong; Gao, Xin-Fen; Xu, Bo (Phytotaxa, 2021)
Primula dujiangyanensis, a new species from Dujiangyan, Sichuan of China, is described and illustrated here. The new species is morphologically similar to P. kialensis and P. pengzhouensis, but it can be distinguished from the latter species by dense white hairs at roots, long stolons, smaller plants and leaves, solitary scape arising from leaf rosette, single lanceolate bract, and shorter pedicel, and it also showed different positions of anthers and styles in the corolla tube.